Report of an ad hoc Panel on the Applications of Biotechnology to Traditional Fermented Foods (Washington, D.C., 1992)
The report discusses opporttunities for the application of biotechnology to traditional femented food. Scientists from developed and developing countries describe their research in this field and provide thier recommendations on priorities for future research.
Keywords: Fermented foods,Thực phẩm lên men